Episodes of seabed rise and rapid drowning controlling the development of regressive and transgressive rhodolithic limestones in a tectonically-active subduction setting (Early Miocene, Wairarapa region, New Zealand). Issue 1 (2nd January 2022) - Caron, Vincent; Bailleul, Julien; Chanier, Frank; Mahieux, Geoffroy
ABSTRACT: Early Miocene limestones from the Wairarapa region of New Zealand were deposited on thrust-bounded margins of trench-slope basins, and consist of two superposed stratal units, namely units A and B, interpreted as forced regressive and forced transgressive foralgal and rhodolith-bearing deposits, respectively. Unit A is floored by a regressive surface of marine erosion cut into shelfal to bathyal siliciclastic successions, and is overlain across a transgressive surface of erosion by Unit B. A drowning surface abruptly places the latter deposits in contact with deeper hemipelagites and turbidites. The succession is explainable within a tectono-eustatic based framework as follows: (1) Structurally controlled rapid relative sea-level fall, (i.e. sea-bed rise), from upper bathyal to shelfal depths promoted development of regressive ('lowstand') mixed carbonate–siliciclastic deposits. Continuation of seabed rise resulted in deposition of pure carbonate sediments, which are represented by channel-fill rhodolithic rudstones; (2) early stage of relative sea-level rise (i.e. seabed drowning) caused emplacement of transgressive glauconitic limestones, consisting of either foralgal deposits, or incised rhodolithic limestones; (3) continued relative sea-level rise terminated carbonate production. The present study documents carbonate production and termination in a tectonically active and confined intra-slope setting, reflected in the development and distribution of unusual forced regressive, and transgressive rhodolithic-heterozoan carbonates.